Implementasi REST-API untuk Sistem Informasi Administrasi di Redha Wedding Jakarta - Debby Ramadhina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The Redha Wedding Jakarta is a business entity engaged in services that help plan and implement a series of wedding parties or certain other events in accordance with the schedule and budget that has been set with various concepts offered. Currently, Redha Wedding Jakarta performs services and administrative processes manually. Customers are required to come to the location to exchange information and services, then customers process payments and get a note based on the results of an interview with Redha Wedding Jakarta. However, this system has several obstacles such as customers are required to come to the location to exchange information and see existing services, manual recording processes that can cause customer data loss. To overcome this problem there is a solution, namely by using the website. The website can facilitate the exchange of information, the administrative process with customers becomes easier, and also as a promotional medium because it can be accessed anywhere and anytime. It is expected that the new information administration system using the Representational State Transfer method equipped with Application Programming Interface technology can overcome existing problems. Keywords : Representational State Transfer, Application Programming Interface, Information System Administration, Wedding, Website